Business plans handbook. a compilation of business plans developed by individuals throughout North America - Pearce, Lynn M. (Gale virtual reference library, 2010)
Actual business plans compiled by, and aimed at, entrepreneurs seeking funding for small businesses. Presents sample plans taken from businesses in the manufacturing, retail and service industries which serve as examples of how to approach, structure and compose business plans.